Analisis Efektivitas Pengelolaan Dana Desa dalam Meningkatkan Pertumbuhan Ekonomi dan Infrastruktur Pedesaan : (Studi Kasus: Nagari Aua Kuniang, Kec. Pasaman, Kab. Pasaman Barat) - Meliza Dara Puspita; Sandra Dewi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research was motivated by community complaints regarding the innefective management of village funds in increasing economic growth and rural infrastructure in Nagari Aua Kuniang. The Nagari government explained the work program carried out to increase community income, but contrary to the reality on the ground, the work program carried out was not appropriate with community needs. The aim of this research is first, to find out how the village fund management mechanism, is second what are the implications of village fund managemnet in increasing economic growth and rural infrastructure, and third what is the effectiveness of village fund management in increasing economic growth and rural infrastructure in Nagari Aua Kuniang District Pasaman, West Pasaman Regency. This type of research is field research with a qualitative descriptive approach. The informants in this research were Wali Nagari Aua Kuniang, Head of General Affairs and Finance, Head of Welfare and Services, and two community figures. The data obtained in this research came from observations, documentation, and interviews which were then analyzed using data reduction techniques, data preparation, and drawing conclusions and the research time started from June 2024 until completion. The results of this research indicate that the management of village funds in Nagari Aua Kuniang, Pasaman District, West Pasaman Regancy cannot be said to be effective because it is not in accordance with existing regulations, namely to increase economic growth and rural infrastructure. The nagari government it self has explained the word program carried out to increase community income, however people just know how it is used but it doesn’t match what they receive and feel, in fact Aua Kuniang wrote thet Vastuk’s vast potential has been explored.